2017
DOI: 10.1016/j.atherosclerosis.2017.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of 14q32 microRNA miR-495 reduces lesion formation, intimal hyperplasia and plasma cholesterol levels in experimental restenosis

Abstract: GSO-495 administration decreased our primary outcomes, namely intimal hyperplasia, and accelerated atherosclerosis. GSO-495 administration also favourably affected multiple secondary outcomes, including macrophage influx, plaque stability and total plasma cholesterol levels. We conclude that 14q32 microRNA miR-495 is a promising target for prevention of restenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 32 publications
4
30
0
1
Order By: Relevance
“…As ‘snoRnome-wide’ screening methods are not yet readily available, we selected a specific subset of snoRNAs and measured these by rt/qPCR, in order to determine whether or not snoRNAs may be suitable as biomarkers for either exercise or muscle recovery. We selected seven snoRNAs that are expressed from a single gene locus, 14q32, which also encodes 54 microRNA genes, including miR-495-3p, that we know are involved in angiogenesis and vascular remodeling ( Welten et al, 2014 , 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…As ‘snoRnome-wide’ screening methods are not yet readily available, we selected a specific subset of snoRNAs and measured these by rt/qPCR, in order to determine whether or not snoRNAs may be suitable as biomarkers for either exercise or muscle recovery. We selected seven snoRNAs that are expressed from a single gene locus, 14q32, which also encodes 54 microRNA genes, including miR-495-3p, that we know are involved in angiogenesis and vascular remodeling ( Welten et al, 2014 , 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…In another study, miR-495 was thus shown to not only contribute to atherosclerotic lesion formation, but also plaque stability in ApoE −/− mice. Inhibition of miR-495 reduced intimal hyperplasia and decreased accelerated atherosclerosis and plasma cholesterol levels (83). A recent study revealed that activation of the NLRP3 inflammasome occurred after cerebral I/R, suggesting that initially microglia are the main source of activated NLRP3 inflammasomes, and in the later stages, the NLRP3 inflammasome is activated within neurons and vascular EC (84).…”
Section: Nlrp3 and Cvdsmentioning
confidence: 99%
“…For example, inhibition of miR-329, miR-494, miR-487b, and miR-495 in mice stimulated neovascularization after hind limb ischemia (16), but inhibition of miR-494 in mice also decreased atherosclerosis and increased plaque stability (17). Moreover, inhibition of miR-495 reduced accelerated atherosclerosis and intimal hyperplasia in mice (18). Furthermore, miR-487b plays a role in angiotensin II-induced aneurysm formation in rats (19).…”
Section: Introductionmentioning
confidence: 99%